Local Wisdom BÃ¢burughÃ¢n BeccÃ¨’ in Madurese Proverb to Maintain Local Content Learning in Islamic Boarding School - Effendy, Moh Hafid; Putikadyanto, Agus Purnomo Ahmad; Ayuanita, Kristanti; Supandi (TADRIS: Jurnal Pendidikan Islam, 2022)
Madurese proverb is one of the traditional expression of Madurese ethnic which contains various bÃ¢burughÃ¢n beccÃ¨’ or advice which contains values. One of the highest values â€‹â€‹held by the Madurese community is religious values â€‹â€‹which are based on the strength of belief in Islam. The expression that still remains a strength in maintaining Madurese local wisdom is the existence of the application of religious values â€‹â€‹contained in Madurese proverb. The identity of the attitude of the Madurese community is embedded in traditional expressions, namely in proverbs that become advice in every mindset and philosophical attitude of the Madurese community. The purpose of this study is to describe the form of bÃ¢burughÃ¢n beccÃ¨’ in Madurese proverbs in order to maintain Madurese local wisdom in social reality in Islamic boarding schools. This study uses a qualitative approach with a phenomenological type of research. Sources of data in this study consisted of kyai, lora, and students in one Islamic boarding school in Pamekasan Regency. The results showed that there was a form of bÃ¢burughÃ¢n beccÃ¨’ or advice in Madurese proverbs which were expressed in the form of religious values, character education, and socio-cultural values. So it can be said that nature, objects, and the surrounding environment shape the attitude and character of the religious Madurese community.